RISK ASSESSMENT OF TRANSGENIC COTTON HARBORING BT AND GLYPHOSATE RESISTANCE GENE ON FISH (Labeo rohita) - A. A. Shahid; T. Haider; T. R. Samiullah; M. A. Ali; K. S. Bajwa; A. Q. Rao; I. B; Salisu; T. Husnain (Journal of Animal and Plant Sciences, 2019)
Assessment of potential risk of transgenic Bt protein on Rohu fish (Labeo rohita) was done. This sensitive vertebrate is an important part of the food chain and is commonly eaten in Pakistan. Comparative analyses on Labeo rohita were performed in three groups i.e. fish fed with Bt diet, non Bt diet and glyphosate resistant protein containing diet to evaluate the differences in their morphological, histological, biochemical and molecular characteristics. No noticeable difference was observed in morphologies as well as biochemical activities of organs. The analysis include glucose, ascorbic acid, total lipids, cortisol, glycogen, phospholipids, cholesterol, triglycerides and free fatty acid test. Structural and morphological bone analyses did not show any deformities, holes and unusual bends which concluded non-significant effect of modified diet. The presence of Cry and Cp4EPSPS protein in experimental samples was confirmed through ELISA. The biochemical and molecular analysis also confirmed that, there was no negative effect of Cry and Cp4EPSPS protein on fish.
Keywords: Bt Cotton; Glyphosate; Labeo rohita; resistance; transgenic